Apresentação PBCIB n.2 v.7, 2012 - Freire, Gustavo Henrique de Araújo; Freire, Isa Maria; Araújo, Vânia Maria Rodrigues Hermes de (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Apresentação PBCIB n.2 v.7, 2012